Pengaruh Program Pusat Informasi Dan Konseling Remaja (PIK-R) Terhadap Pengetahuan, Sikap Dan Tindakan Kesehatan Reproduksi Remaja Di SMAN 1 Selesai Tahun 2024 - Tifani Hadi Tri Wahyuni; Nurhayani Harahap (STIKES Columbia Asia Medan, 2024)
The Adolescent Information and Counseling Center (PIK-R) is an integral part of the GenRe program, designed specifically to provide adolescents with guidance and information on topics such as marriage readiness, family roles, the KRR TRIAD, life skills, gender, advocacy, and KIE competencies. Based on the 2019 SKAP data, a substantial number of respondents—predominantly those with lower education levels (60.1%) and those living in rural areas (59.22%)—demonstrated limited knowledge about family planning (75.2%), reproductive health (34.4%), GenRe (81.6%), and Adolescent Family Building (87.9%). Furthermore, 9.8% of adolescents were not receiving any related information. Against this backdrop, a study was conducted in 2024 to examine the effect of the PIK-R program on adolescent reproductive health knowledge, attitudes, and behaviors at SMAN 1 Selesai. This analytical cross-sectional study involved 98 students who met the inclusion criteria, with data analyzed using chi-square tests and binary logistic regression. The results showed that the PIK-R program significantly improved knowledge and behaviors related to adolescent reproductive health but did not affect attitudes. It is recommended that supervisors encourage student participation in PIK-R activities, enhance scheduling to maximize exposure to reproductive health education, and perform comprehensive evaluations of the program's effectiveness.